Pengaruh Profil Demografis Terhadap Keberhasilan Pelatihan Pengolahan Pupuk Organik di Kecamatan Ngadirojo Kabupaten Wonogiri - Shanti Emawati; Sudiyono Sudiyono; Ayu Intan Sari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2017)
The aim of this study was to analyse the impact of demographic profile to acceptability of the training of organic fertilizer processing in Ngadirejo, Wonogiri. This study was performed in Ngadirejo, Wonogiri, at Agustus 1 to September 28, 2016. The design of this study was pre-experimental design with one group pretest and posttest design. Techniques for location and respondent determinations were purposive sampling. The data used in this study consisted primary data collected from beef cattle farmers who follow the tarining of organic fertilizer processing and secondary data which is obtained from related agencies. The data has been analyzed using paired sample t test and multiple linear regressions. The results showed that education level, age, the number of animal had by farmer, and occupation of the farmers collectively affected acceptability of the organic fertilizer processing training, on the other hand, education level, age, the number of animal had by farmer, and occupation of the farmers partially did not affect acceptability of the organic fertilizer processing training.